Scope of Non-estrogenic Steroidal Congeners against Breast Cancer (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
Various novel non-estrogenic steroidal D-ring substituted analogs were synthesized and evaluated for their breast cancer activity against human breast cancer cell lines. The good cytotoxic results obtained against the breast cancer cell lines throws new insights into the field as the analogs are non 17β –Hydroxy estrogenic derivatives which are considered to be pivotal for the potent estrogenic activity. The synthesized steroidal analogs provide a very good platform for mechanistic studies of the interaction between non-esterogenic steroids and estrogen receptors.